2014
DOI: 10.1371/journal.pone.0101993
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of La Antigen Exerts Potential Antiviral Effects against Hepatitis A Virus

Abstract: BackgroundDespite the development and availability of hepatitis A virus (HAV) vaccine, HAV infection is still a major cause of acute hepatitis that occasionally leads to fatal liver disease. HAV internal ribosomal entry-site (IRES) is one of the attractive targets of antiviral agents against HAV. The aim of the present study is to evaluate the impact of La, one of the cellular proteins, on HAV IRES-mediated translation and HAV replication.Methods and FindingsWe investigated the therapeutic feasibility of siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…We observed that HAV RNA levels were inhibited in Huh7 cells treated with Japanese miso extracts (Figure 2 c). For virus titration, although PCR may not be suitable to measure the viral titers, our previous study 17 showed the results of our real-time RT-PCR system are well correlated with those of HAV titers evaluated by ELISA 18 .…”
Section: Resultsmentioning
confidence: 75%
“…We observed that HAV RNA levels were inhibited in Huh7 cells treated with Japanese miso extracts (Figure 2 c). For virus titration, although PCR may not be suitable to measure the viral titers, our previous study 17 showed the results of our real-time RT-PCR system are well correlated with those of HAV titers evaluated by ELISA 18 .…”
Section: Resultsmentioning
confidence: 75%
“…4c,d). To further test whether NOT inhibited inflammation through JAK1/2 and STAT3/5, we treated macrophages with the JAK1/2 inhibitors, including SD1029, AG490 and Ruxolitinib 35 , and the STAT3/5 inhibitor SH-4-54 36 . All of these inhibitors could markedly inhibit the production of CXCL10, CCL5, IL-1β, or NOS2 at mRNA or at protein levels in TNFα-or LPS/IFNγ-treated macrophages ( Fig.…”
Section: Not Inhibits Jak-stat Activation To Attenuate Inflammationmentioning
confidence: 99%
“…The key host enzymes and cellular factors that are required for the viral lifecycle are targets of antiviral therapies. 65 Several cellular proteins, such as autoantigen La, 66 glyceraldehyde-3-phosphate dehydrogenase (GAPDH), 67 , 68 polypyrimidine tract-binding protein (PTB/hnRNPI), 68 70 poly(C) binding protein 2 (PCBP2/hnRNP-E2), 71 polyadenylate-binding protein-1 (PABP), 72 eukaryotic translation initiation factor 4E (eIF4E) 73 and eukaryotic translation initiation factor 4G (eIF4G), 72 , 74 , 75 interact with HAV IRES RNA. These proteins might be associated with HAV replication.…”
Section: Htas Against Havmentioning
confidence: 99%
“… 65 The janus kinase (JAK) inhibitors SD-1029 and AG490 reduced La protein expression and inhibited HAV IRES activities and HAV replication in African green monkey kidney GL37 cell lines. 65 We also found that the JAK2 inhibitor AZD1480 inhibited the expression of phosphorylated-(Tyr-705)-signal transducer and activator of transcription 3 (STAT3) and La and inhibited HAV IRES-mediated translation and HAV replication in human hepatoma cell lines. 15 Thus, La plays a role in HAV replication and might be an important target of HAV therapy.…”
Section: Htas Against Havmentioning
confidence: 99%
See 1 more Smart Citation